Occupation, work load and the size and shape of lumbar vertebral canals. - Vanharanta, H.; Heliovaara, M.; Korpi, J.; Troup, J. D. (Scandinavian Journal of Work, Environment & Health, 1987)
Measurements made from plain lumbar radiographs were used to compare the size and shape of the lumbar vertebral canals between various categories of occupation and work load among 77 men and 118 women with a history of low-back pain. The mean anteroposterior foraminal diameters proved to be wider in female farm workers than in other women, especially in the vertebra L3 (17.1 versus 15.4 mm). However, the men who did heavy manual work had smaller anteroposterior foraminal diameters than the men whose work involved less physical labor (difference at L5 9.4 versus 10.8 mm). Female farm workers were found to have shorter interarticular distances than females in other occupational groups. In the men who reported working in stooped postures or reported lifting and carrying heavy objects at work, the interarticular distances were wider than in men who had no such exposures.